Genital Micro-Organisms in Pregnancy - Bagga, Rashmi; Arora, Parul (Frontiers in Public Health, 2020)
The microbiome of the female genital tract may undergo changes in pregnancy due to metabolic, endocrinological and immunological alterations. These dysbiotic states may cause infections which may ascend upwards to the feto-placental unit or may be seeded hematogenously. These low grade and often low virulent infectious states lead to chronic inflammatory states and maybe associated with adverse maternal and neonatal outcome. Organisms have been isolated from amniotic fluid and placentae from women delivering pre-term; however the possibility of contamination cannot be conclusively ruled out. Common vaginal dysbiotic states often cause symptoms that are overlooked and often untreated. Vulvovaginal Candidiasis (VVC); Bacterial Vaginosis (BV)Trichomonas Vaginitis (TV) are the commonly occurring dysbiotic states leading to vaginal infective state in pregnancy. With the advent of novel technologies like Next Generation sequencing, it will soon be possible to comprehensively map the vaginal microbiome and assess the interplay of each microbial state with their effects in pregnancy. This may open new avenues for antibiotic recommendations, probiotics and potential alternate therapies for dysbiotic states leading to pregnancy complications.